Hubungan Antara Pengetahuan Gizi, Status Gizi dan Kepatuhan Konsumsi Tablet Tambah Darah (TTD) dengan Kejadian Anemia Pada Remaja Putri di SMK Al-Ishlah Singaparna Tahun 2023 - Nuraina, Viana Fauzia; Sulistyoningsih, Hariyani (Universitas Galuh, 2023)
Anemia is a significant health problem in Indonesia, with a prevalence of 57.7% among adolescents in the Singaparna Health Center area. This study aims to evaluate the relationship between nutritional knowledge, nutritional status, and adherence to the consumption of Blood Added Tablets (TTD) with the incidence of anemia in adolescent girls at SMK Al-Ishlah in 2023. Quantitative research with a cross-sectional approach involved 47 adolescent girls as a sample. Data analysis using SPSS showed that there was no significant relationship between nutritional knowledge (p = 0.654), nutritional status (p = 0.442), and TTD consumption compliance (p = 1,000) with the incidence of anemia. Research recommendations include cooperation between schools and health services to improve adolescent nutrition, monitoring of anemia prevention, nutrition education policies in schools, nutrition campaign programs, educational activities, and developing effective strategies. This study contributes to the development of public health science related to nutrition and anemia.